Effects of hot‐water and steam blanching of sliced potato on polyphenol oxidase activity. (21st September 2018) - Moscetti, Roberto; Raponi, Flavio; Monarca, Danilo; Bedini, Giacomo; Ferri, Serena; Massantini, Riccardo
Summary: The worldwide potato production is considered the fourth‐most important food sector due to the increasing use of potatoes as raw materials for high‐convenience food. Enzymatic browning, due to polyphenol oxidase (PPO), is related to unacceptability by consumer. Among antibrowning agents, thermal treatments are viable alternatives. In this study, the efficacy of hot‐water and steam blanching at 80–90 °C of potato slices (1‐cm thick) was evaluated in terms of colour changes as well as PPO inactivation kinetics, substrate specificity and transition state parameters. In general, all treatments [1] bleached the slices, [2] inactivated PPO and [3] reduced its kinetic efficiency. Results from thermal inactivation kinetics promoted hot‐water blanching at 90 °C for approx. 2 min as the fastest treatment to obtain enzymatic‐stable potato slices. Moreover, steam blanching required more energy (53.93 ± 1.24 kJ mol −1 ) than hot‐water treatment (41.41 ± 4.51 kJ mol −1 ) to reach the transition state and then to unfold the PPO enzyme. Abstract : Step‐by‐step representation of the experimental activity: (a) sample preparation, (b) blanching treatments, (c) measurement of the catalytic efficiency of the polyphenol enzyme and (d) analysis of the thermal inactivation kinetics.